Antibacterial Activity of Black Garlic against Foodborne Pathogens: A Review - Abiyyuddin, M. Farras; Fitrania, Fathika; Jannah, Mirriyadhil (Jurnal Teknologi Pangan, 2025)
Foodborne diseases have become a serious global public health threat, one of which is caused by the consumption of food contaminated by pathogenic bacteria. Efforts to control such contamination can be carried out through the use of antibacterial agents derived from natural sources. Black garlic, a aged product of fresh garlic, is known to possess various biological effects, including antibacterial activity. Several studies have reported that black garlic exhibits antibacterial activity against various foodborne pathogenic bacteria, such as Staphylococcus aureus, Escherichia coli, Salmonella spp., and Pseudomonas aeruginosa. This review aims to analyze the antibacterial activity of black garlic against foodborne pathogens. The review methodology followed the PRISMA-study. Literature searches were conducted using Google Scholar, PubMed, and ScienceDirect databases, with the keywords “black garlic”, “antimicrobial”, “antibacterial”, and “foodborne pathogens”, yielding 16 articles that met the inclusion criteria. The findings indicate that black garlic demonstrates antibacterial activity against both Gram-positve and Gram-negative bacteria. These results underscore the potential of black garlic as a natural antibacterial agent for controlling foodborne pathogens.